2019
DOI: 10.1177/1352458519872751
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography and multiple sclerosis: Update on clinical application and role in clinical trials

Abstract: Optical coherence tomography (OCT) has emerged as a fast, non-invasive, inexpensive, high-resolution imaging technique in multiple sclerosis (MS). Retinal layer quantification by OCT facilitates a ‘window’ into not only local retinal pathology but also global neurodegenerative processes, recognised to be the principal substrates of disability accumulation in MS. While OCT measures in MS have been demonstrated to reflect visual function, inflammatory activity outside of the visual pathways, disability measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 119 publications
(165 reference statements)
0
38
0
2
Order By: Relevance
“…Third, we investigated whether ceramide levels correlate with optical coherence tomography (OCT) measures of retinal atrophy, which have been shown to reflect global disease processes in MS, and provide an opportune site to study and monitor neuro-axonal loss. 17 Finally, we investigated whether there are associations between serum ceramide and serum neurofilament light chain (sNfL) levels, which has been proposed as a biomarker of neuro-axonal injury in MS. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…Third, we investigated whether ceramide levels correlate with optical coherence tomography (OCT) measures of retinal atrophy, which have been shown to reflect global disease processes in MS, and provide an opportune site to study and monitor neuro-axonal loss. 17 Finally, we investigated whether there are associations between serum ceramide and serum neurofilament light chain (sNfL) levels, which has been proposed as a biomarker of neuro-axonal injury in MS. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…Although MRI is a widely accepted paraclinical tool in the diagnosis of MS, its main limitation is its low specificity [4,5]. In recent years, OCT has proven to be a promising diagnostic method and has been gradually incorporated in MS scientific and clinical research [12,32]. In this cross-sectional study, we aimed to investigate the applicability of OCT in the differential diagnosis of MS and NSWMLs patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that thinning of the GCIPL and mRNFL increased the risk of MS diagnosis in our group of patients, while GCIPL thickness was the best OCT marker discriminating MS from NSWMLs patients. pRNFL thickness represents the most intensively studied and widely used OCT parameter in MS [32][33][34][35]. The results of longitudinal studies showed the prognostic value of pRNFL thickness for the prediction of clinical progression (disability worsening and relapse) and its high sensitivity to inflammatory changes and damage caused by ON [33,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of these diffuse CNS pathologies in progressive MS are complex but may include transneuronal degeneration due to the destruction of efferent/afferent projections [18], B cell-rich meningeal inflammation [19], the accumulation of peripheral immune cells in the choroid plexus stroma [20], chronically active and slowly expanding lesions with smoldering inflammation [21], accelerated biological aging [22], or complement activation [23]. Different aspects of the described progressive MS pathologies can be visualized by different imaging techniques, including positron emission tomography (PET) imaging, advanced magnetic resonance imaging (MRI), brain volume measurement, optical coherence tomography (OCT), diffusion tensor imaging (DTI), or myelin water imaging (MWI) [24][25][26][27][28].…”
Section: General Aspects Of Ms Pathology and The Relevance Of Glial Cmentioning
confidence: 99%